PEMODELAN ANTRIAN SISTEM PENGAMBILAN PESANAN PRODUK PADA GUDANG MINUMAN RINGAN DENGAN SISTEM RAK DRIVE-IN - M Zaky Hadi, Taufik Djatna, dan Sugiarto (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
This paper proposed a queue model for beverage order picking system produced from agricultural commodity in warehouse with drive-in rack system in order to analyze and increase the warehouse performance. A (M/M/C):(GD/N/∞) queue approach was used to build the model with the queue approach. This paper considered total operator must-be-assigned to improve queue time (Wq), queue length, and utilization in the warehouse. Stack, queue, linked list, Colour HSB (Hue, Saturation, Brightness) algorithms were used to represent drive-in rack, product queuing, and product status in the warehouses. The model was implemented in computer simulation using java programming. After build the model, a real case industrial problem was presented to test the model. The model could calculate warehouse performance including low performance in racking, transportation to loading area, and loading process for current number of operators and idle operator in the warehouse process. This result was in line with the industry condition that has over capacity and high product bottlenecks in the warehouse. The model was used to find and analyze total operator-must-assigned to increase the warehouse performance. The computer simulation showed colour changing based on density of product stack in queue area. This colour degradation helped for easier understanding and accelerating product status detection (including hold, ready-to-release, and expired beverage products in the warehouse).Keywords:beverage warehousing, drive-in rack, order picking, queue modelling, queueing theory